"The international schools are not so international after all": The educational experiences of Third Culture Kids. Issue 1 (2nd January 2018) - Lijadi, Anastasia Aldelina; van Schalkwyk, Gertina J.
Abstract : One of the significant adaptations needed by children of high-mobility families when moving to a new country is adjustment to the education system. This exploratory study reports on the lived experiences and opinions from three cohorts of adult Third Culture Kids (TCK) during their primary and secondary education ( N  = 33). We explored the school experiences of TCK over the past four decades in view of the rising number of international schools worldwide to meet the demands of internationally mobile families. Field texts were collected using online Facebook asynchronous focus groups, and the narrative analysis revealed the challenges TCK faced regarding accessibility, the introduction of new curricula, and the language of instruction at international schools. For the most part these changes have been made in support of TCK's education experience after repatriation. However, the changing profiles of school-going students in international schools in the 21st century have seemingly made the international schools not as international as before. We discuss this theme and the challenges young TCK might face attending an international school and adjusting to a new environment after every move, as well as the implications of this study for parents of TCK and school psychologists assisting this unique school-going population worldwide.